The role of IQSEC2 in syndromic intellectual disability: Narrowing the diagnostic odyssey. Issue 10 (17th August 2017) - Helm, Benjamin M.; Powis, Zoe; Prada, Carlos E.; Casasbuenas‐Alarcon, Olga L.; Balmakund, Tonya; Schaefer, G. B.; Kahler, Stephen G.; Kaylor, Julie; Winter, Susan; Zarate, Yuri A.; Schrier Vergano, Samantha A.
Abstract : While X‐linked intellectual disability (XLID) syndromes pose a diagnostic challenge for clinicians, an increasing number of recognized disorders and their genetic etiologies are providing answers for patients and their families. The availability of clinical exome sequencing is broadening the ability to identify mutations in genes previously unrecognized as causing XLID. In recent years, the IQSEC2 gene, located at Xp11.22, has emerged as the cause of multiple cases of both nonsyndromic and syndromic XLID. Herein we present a case series of six individuals (five males, one female) with intellectual disability and seizures found to have alterations in IQSEC2 . In all cases, the diagnostic odyssey was extensive and expensive, often including invasive testing such as muscle biopsies, before ultimately reaching the diagnosis. We report these cases to demonstrate the exhaustive work‐up prior to finding the changes in IQSEC2 gene, recommend that this gene be considered earlier in the diagnostic evaluation of individuals with global developmental delay, microcephaly, and severe, intractable epilepsy, and support the use of intellectual disability panels including IQSEC2 in the first‐line evaluation of these patients.